Controlled dietary phosphate loading in healthy young men elevates plasma phosphate and FGF23 levels - Gerber, Jennifer Scotti; Arroyo, Eva Maria Pastor; Pastor, Johanne; Correia, Miguel; Rudloff, Stefan; Moe, Orson W.; Egli-Spichtig, Daniela; Mohebbi, Nilufar; Wagner, Carsten A. (Pflügers Archiv, 2025)
Increased dietary inorganic phosphate (P i ) intake stimulates renal P i excretion, in part, by parathyroid hormone (PTH), fibroblast growth factor 23 (FGF23) or dopamine. High dietary P i may also stimulate sympathetic outflow. Rodent studies provided evidence for these regulatory loops, while controlled experiments in healthy humans examined periods of either a few hours or several weeks, and often varied dietary calcium intake. The effects of controlled, isolated changes in dietary P i intake over shorter periods are unknown. We studied the effects of a low or high P i diet on parameters of mineral metabolism in 10 healthy young men. Participants received a standardized diet (1000 mg phosphorus equivalent/day) supplemented with either a phosphate binder (low P i diet) or phosphate capsules (750 mg phosphorus, high P i diet) in a randomized cross-over trial for 5 days with a 7-day washout between diets. High P i intake increased plasma P i levels and 24-h excretion and decreased urinary calcium excretion. High P i intake increased intact FGF23 (iFGF23) and suppressed plasma Klotho without affecting cFGF23, PTH, calcidiol, calcitriol, Fetuin-A, dopamine, epinephrine, norepinephrine, metanephrine, or aldosterone. Higher iFGF23 correlated with lower calcitriol and higher PTH. These data support a role for iFGF23 in increasing renal P i excretion and reducing calcitriol in healthy young men during steady-state high dietary P i intake. High dietary P i intake elevated blood P i levels in healthy young subjects with normal renal function and may therefore be a health risk, as higher serum P i levels are associated with cardiovascular risk in the general population.